Full-length transcriptome reveals the pivotal role of ABA and ethylene in the cold stress response of Tetrastigma hemsleyanum - Qian, Lihua; Yin, Shuya; Lu, Na; Yue, Erkui; Yan, Jianli (Frontiers in Plant Science, 2024)
Tetrastigma hemsleyanum is a valuable herb widely used in Chinese traditional and modern medicine. Winter cold severely limits the artificial cultivation of this plant, but the physiological and molecular mechanisms upon exposure to cold stress in T. hemsleyanum are unclear. T. hemsleyanum plants with different geographical origins exhibit large differences in response to cold stress. In this research study, using T. hemsleyanum ecotypes that exhibit frost tolerance (FR) and frost sensitivity (FS), we analyzed the response of cottage seedlings to a simulated frost treatment; plant hormones were induced with both short (2 h) and long (9 h) frost treatments, which were used to construct the full-length transcriptome and obtained 76,750 transcripts with all transcripts mapped to 28,805 genes, and 27,215 genes, respectively, annotated to databases. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed enrichment in plant hormone signaling pathways. Further analysis shows that differently expressed genes (DEGs) concentrated on calcium signaling, ABA biosynthesis and signal transduction, and ethylene in response to cold stress. We also found that endogenous ABA and ethylene content were increased after cold treatment, and exogenous ABA and ethylene significantly improved cold tolerance in both ecotypes. Our results elucidated the pivotal role of ABA and ethylene in response to cold stress in T. hemsleyanum and identified key genes.